2022
DOI: 10.1016/j.gerinurse.2021.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Infection prevention and control in nursing homes during COVID-19: An environmental scan

Abstract: To examine processes and programmatic elements of infection prevention and control (IPC) efforts and identify themes and promising approaches in nursing homes (NHs), an environmental scan was conducted. Data sources included a literature search, relevant listservs and websites, and expert consensus based on a virtual summit of leaders in IPC in long-term care settings. Three thematic areas emerged which have the potential to improve overall IPC practices in the long-term care setting: staffing and resource ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 45 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…Factors that contribute to barriers to infection control observed by our team include the communal living environment, the large number of staff needed to care for the residents, including certified nursing assistants (CNA), licensed practical nurses (LPN), registered nurses (RN), dietary staff, therapy staff, activity staff, social work, environmental services, maintenance staff, and the number of volunteers and visitors entering the facility. This is similar to findings found in the literature [ 22 ]. Additional contributors are residents with multiple medical comorbidities that increased infection risk whether through immune suppression or cognitive impairment that leaves affected residents unable to comply with the infection control policies meant to protect them.…”
Section: Editorialsupporting
confidence: 93%
See 1 more Smart Citation
“…Factors that contribute to barriers to infection control observed by our team include the communal living environment, the large number of staff needed to care for the residents, including certified nursing assistants (CNA), licensed practical nurses (LPN), registered nurses (RN), dietary staff, therapy staff, activity staff, social work, environmental services, maintenance staff, and the number of volunteers and visitors entering the facility. This is similar to findings found in the literature [ 22 ]. Additional contributors are residents with multiple medical comorbidities that increased infection risk whether through immune suppression or cognitive impairment that leaves affected residents unable to comply with the infection control policies meant to protect them.…”
Section: Editorialsupporting
confidence: 93%
“…From an infection prevention point of view, we need to start by identifying how strong our current infection prevention strategies are in the SNF setting and ensure there is an infection preventionist for every site [ 6 , 7 ]. It would be important to then leverage leadership to help perform additional needs assessments that include communication, equipment resources, staffing resources and training, and community outreach [ 22 , 23 ].…”
Section: Editorialmentioning
confidence: 99%
“…20 Furthermore, an environmental scan identified training and knowledge in infection control as one of the areas to improve NH infection prevention and control during COVID-19 pandemic. 21 Despite these findings regarding the role of IP training in infection control, there is wide variation in IP training standards across NHs. 18 About 46% of NHs in the national survey reported that their IP had no specific infection control training, and most of them were not certified or trained in infection control.…”
Section: Discussionmentioning
confidence: 99%
“…Identifying methods to increase the number of public health professionals capable of responding to emerging health threats is also included as part of national public health objectives,19 and the COVID-19 pandemic only reinforced its importance. In particular, methods to enhance healthcare IPC capacity among the public health workforce were needed to ensure that health department staff were prepared to support nursing homes in preventing and responding to the high incidence of COVID-19,4,5 as nursing homes commonly experience high healthcare personnel turnover and lack time and other resources for IPC training 20. Evaluation findings suggest that the CDC's virtual COVID IPC 101 course was effective in increasing knowledge and confidence among new or less-experienced HAI/AR Program staff in supporting COVID-19 healthcare IPC for nursing homes.…”
Section: Discussionmentioning
confidence: 99%